Quantum potero voce contendam. La Pro Ligario di Cicerone nel giudizio di Quintiliano - Quantum potero voce contendam. Quintilian on Cicero's Pro Ligario - Alfredo Casamento (Ciceroniana On Line)
The paper analyses one of the last voices of the Ciceronian oratory, the Pro Ligario. After a reconstruction of the context in which the oration was produced, the attention is focused on the reception of the text by Quintilian, who on several occasions in the Institutio oratoria shows particular interest for the multiple problems connected to it, identifying the peculiar characteristics.